Increasing the Productivity of Oil Palm (Elaeis guineensis Jacq) Farmers in Tebing Linggahara Baru Village, Bilah Barat District, Labuhanbatu Regency - Aulia Fakhrezi; Khairul Rizal; Yudi Triyanto; Dini Hariyati Adam (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Oil palm has significant potential as a strategic commodity to enhance farmers' income while contributing substantially to Indonesia's foreign exchange earnings. This study aims to examine the role of farmer groups in supporting the productivity of smallholder oil palm farmers. The research was conducted in Tebing Linggahara Baru Village, Bilah Barat District, Labuhanbatu Regency. An associative research design with a descriptive-quantitative survey method was employed. Data were collected through questionnaires and documentation from 30 farmer respondents. Statistical analyses included partial difference tests (t-tests), significance tests (F-tests), and coefficients of determination (R²), which were processed using SPSS. The findings indicate that farmer groups play a crucial role in enhancing the productivity of oil palm farmers.